2010
DOI: 10.1080/15567030802612077
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sulfur- and Nitrogen-containing Organic Species in the Extracts from Pocahontas No. 3 Coal

Abstract: Pocahontas No. 3 coal was extracted with CS 2 , n-hexane, benzene, methanol, acetone, and acetone/CS 2 (1:1 vol/vol) mixed solvent sequentially. The resulting six extracts were analyzed with gas chromatography/mass spectrometer (GC/MS). Hexathiane, octathiocane, 23 sulfur-containing organic species, and 21 nitrogencontaining organic species were detected in the extracts. Sulfur-containing organic species detected in the extracts include dialkyl-and disulfides, dimexano, dibenzothiophene, benzonaphthothiophene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It is well known that benzo [20,21]hopanes 4−7 (C 32−35 , 2) and benzo [16,17,21]hopanes 6,8,9 (C 31−35 , 3) are formed from compound 1 via the cyclization reactions at C20 and C16, respectively. Some compounds with fluorene and acenaphthene moieties (e.g., compounds 4 and 5) in coals should be partially produced from D-ring monoaromatic 8 (14)-secobenzo [20,21]hopanes 6,10,11 (C 32−35 , 6) and 8 (14)-secobenzo [16,17,21]hopanes 11,12 (C 31−35 , 7), which are produced from the corresponding benzohopanes (i.e., compounds 2 and 3) via aromatization and C8−C14 bond cleavage, respectively. Coals are rich in the compounds with two aromatic moieties linked by −(CH 2 ) n −, such as 1-benzylnaphthalene ( 8), but their origin is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that benzo [20,21]hopanes 4−7 (C 32−35 , 2) and benzo [16,17,21]hopanes 6,8,9 (C 31−35 , 3) are formed from compound 1 via the cyclization reactions at C20 and C16, respectively. Some compounds with fluorene and acenaphthene moieties (e.g., compounds 4 and 5) in coals should be partially produced from D-ring monoaromatic 8 (14)-secobenzo [20,21]hopanes 6,10,11 (C 32−35 , 6) and 8 (14)-secobenzo [16,17,21]hopanes 11,12 (C 31−35 , 7), which are produced from the corresponding benzohopanes (i.e., compounds 2 and 3) via aromatization and C8−C14 bond cleavage, respectively. Coals are rich in the compounds with two aromatic moieties linked by −(CH 2 ) n −, such as 1-benzylnaphthalene ( 8), but their origin is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…S‐ heterocyclic aromatics, such as benzothiophene, dibenzothiophene, and benzo[ b ]naphthothiophene along with their alkylated homologues, were identified by GC and GC/MS. In addition, some thiols, sulfides, and disulfides likewise were tentatively detected in the extracts by the high‐resolution MS. Cao et al () also reported dibenzothiophenes, benzo[ b ]naphthothiophenes, and their methylated homologues in the extracts from sequential extraction of Pocahontas No. 3 coal.…”
Section: Small‐molecular Chemicals In Cdls Identified By Gc/msmentioning
confidence: 96%
“…NCCs in extracts from coal extraction and thermal dissolution can more truly represent the original nitrogen forms in coals since the cleavage of covalent bonds involving N almost does not occur during low‐temperature extraction and thermal dissolution. Several investigations have focused on the separation and characterization of NCCs in the extracts from low‐temperature extraction (Ding et al, ; Wei, Wang, & Zong, ; Cao et al, ) and thermal dissolution (Liu et al, ; Wang et al, ) of coals. Ding et al () separated a series of fatty acid amides from Shengli lignite through extraction in carbon disulfide followed by column chromatography and identified by GC/MS.…”
Section: Small‐molecular Chemicals In Cdls Identified By Gc/msmentioning
confidence: 99%
See 1 more Smart Citation
“…Various NCSs were identified from extracts of coals Ding et al, 2008;Zong et al, 2009;Wei et al, 2009;Cao et al, 2010) and reaction mixtures of coals (Wei et al, 2002;Liu et al, 2003), but to the authors' knowledge, no reports were issued on the detection of any NCSs in the products from coal oxidation.…”
Section: Figurementioning
confidence: 97%